Simulations of the CNFETs using different high-k gate dielectrics - Ankita Dixit; Navneet Gupta (Institute of Advanced Engineering and Science, 2020)
In this paper we presented the analysis of Carbon Nanotube Field Effect Transistors (CNFETs) using various high-k gate dielectric materials. The objective of this work was to choose the best possible material for gate dielectric. This paper also presented the study on the effect of thickness of gate dielectric on the performance of the device. For the analysis (19, 0) CNT was considered because the diameter of (19, 0) CNT is 1.49nm and the CNFETs have been fabricated with the CNT diameter of 1.5nm. It has been observed that La2O3 is the best gate dielectric material followed by HfO2 and ZrO2. It was also observed that as thickness of gate dielectric material reduces, drain current of CNFET increases. The outcomes of this study matches with the analytical results and hence confirm the results